The Influence of Social Change on the Shift in Legal Functions (Studies Related to the Development of Information Technology) - Saputri, Ernia Duwi; Prabowo, Andrianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Social change becomes an inevitability in social life, which is then accompanied by changes in existing laws. This legal change is the result of a clash or conflict of attitudes, opinions, behaviors, goals and needs that are always conflicting. This research is a type of normative research. The subject of the study is conceptualized as norms or rules that apply to society and become a reference for everyone's behavior. New discoveries in the field of technology are the impact of social changes that become revolutions, the modernization of education, and so on, which can cause a shift in the function of law. The higher the percentage of information technology users, the higher the opportunity for cybercrime. Thanks to advances in technology, everyone can easily access cyberspace networks. Criminal acts have shifted not only to those contained in the Criminal Code but also clearly give rise to criminal acts that occur through ITE.